UJI BEBERAPA KONSENTRASI EKSTRAK DAUN MIMBA (AZADIRACHTA INDICA A. JUSS.) UNTUK PENGENDALIAN PENYAKIT ANTRAKNOSA YANG DISEBABKAN JAMUR COLLETOTRICHUM CAPSISI PADA BUAH CABAI MERAH PASCA-PANEN - Muhammad Ali; Yunel Venita; Benny Rahman (Jurnal Sagu, 2012)
The objective of this research is to study the effect of some concentrations of neem leaves extractin controlling anthracnose disease on post-harvested red chilli fruits. A research has been conductedexperimentally using a Completely Randomized Design, consisting of 6 treatments and 5 replications. Thetreatments are 6 concentrations of neem leaves extract : 0%=M0, 1%=M1, 5%=M2, 10%=M3, 15%= M4and 20%=M. Result of the research indicated that the concentration of neem leaves extract gave differenteffect in controlling anthracnose disease of the red chilli fruits. The concentration of neem leaves extractat 15% and 20% gave a better effect in controlling anthracnose disease of post-harvested red chilli fruits,which resulted in a smaller diameter of in-vitro fungi colony growth, a longer incubation period of thedisease and a lower incidence of the disease.